University Administration of Federal Grants at the University of Rochester - Comptroller General of the U.S., Washington, DC.; Comptroller General of the U.S., Washington, DC. ([Washington, D.C.]] : Distributed by ERIC Clearinghouse, 1978)
Federal research grant activities at the University of Rochester for the year ending June 30, 1977, during which the university received $38.6 million in grants and contracts, are reviewed. The report includes: (1) a review of the university's system for administering and accounting for these funds; (2) an analysis of selected major grants awarded by the National Institutes of Health and the National Science Foundation (NSF) to determine whether costs claimed were adequately documented and related to the grants' purposes; (3) an evaluation of the adequacy of audit activities by the Defense Contract Audit Agency; and (4) a review of Health, Education, and Welfare and NSF practices for monitoring research grants and coordinating with other federal agencies. A four-page cover letter to the U.S. House of Representatives Subcommittee on Intergovernmental Relations and Human Resources is included. (Author/MSE)
Educational level discussed: Higher Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Agency Cooperation; College Administration; Contracts; Educational Finance; Federal Aid; Financial Support; Foundation Programs; Government School Relationship; Grants; Higher Education; Private Colleges; Recordkeeping; Research Projects; School Accounting; Scientific Research; Grant Administration -- University of Rochester NY; National Institutes of Health -- National Science Foundation -- Research Administration; Reports, Research